To Assess Role of Circulating Micro RNAs in Aplastic Anemia Patients - Sumera Abbasi, Vershia Kanwal, Muhammad Sarwar Khan, Syeda Ghazia Nazim, Kiran Memon, Raima Kalhoro, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Aplastic anemia is an acquired bone marrow failure categorized by marrow hyperplasia due to immune mediated effect on bone marrow. Objective: To assess role of plasma micro RNAs (miR-150-5p) and (miR-146b-5p) in patients of aplastic anemia by (real time PCR technique) and to correlate plasma microRNA’s with severity in patients of aplastic anemia. Methods: Eight ml blood sample was collected from patients, and then distributed into two EDTA tubes. 3 ml EDTA tube was used for Complete blood count (CBC) and 5 ml EDTA sample was used for RNA isolation for performing MicroRNA testing. Bone marrow examination was performed at the department of Pathology, LUMHS Jamshoro, Diagnostic and Research Laboratory at Liaquat University Hospital Hyderabad, and Department of Medicine and Pediatrics at Civil Hospital Hyderabad for diagnosis of Aplastic anemia during July 2019 to December 2019. All the data was recorded via self-made proforma and analyzed by using SPSS version 21. Results: Out of 72 cases, 36 were patients and 36 were controls, males were most common in both groups. According to severity of aplastic anemia 19 (52.8%) patients seen with very severe aplastic anemia, 10(27.8%) found with non-severe aplastic anemia and 7 (19.4%) found with severe aplastic anemia. Micro RNA 150.5p was positive among all patients, while negative in all controls. Micro RNA 146b.5p was positive among 5 patients, while it was negative in all controls p-value 0.001. Mean of micro RNA 150.5p was higher 34.89+13.99 in very severe aplastic anemia, 29.33+1.99 in severe and 28.76+2.37 in non-severe aplastic anemia. There was a negative correlation between Micro RNA 150.5p and hemoglobin, r-value 0.029, negative correlation between Micro RNA 150.5p and WBC, r-value 0.008, strong negative correlation between Micro RNA 150.5p and MCV, r-value 0.408 and weak negative correlation between Micro RNA 150.5p and platelets, r-value 0.017. Conclusion: It was concluded that plasma micro RNA’s (miR-150-5p) is a potential diagnostic marker of aplastic anemia. It was positive among all patients of aplastic anemia and showed a strong negative correlation with haemoglobin level, WBC, MCV and platelets. Keywords: Aplastic Anemia, miR-150-5p, miR-146b-5p, Bio-markers